REPRESENTASI SUARA PEREMPUAN TERHADAP KEKERASAN SEKSUAL DI FILM LIKE & SHARE (2022) - Estadista Herdini, Reyna; Ratri Rahmiaji, Lintang; Lestari, Sri Budi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The film Like & Share (2022) written and directed by Gina S Noer, is a film that discusses sexual violence experienced by women, especially teenagers. The aim of this research is to describe how women's voices are represented regarding sexual violence and to find out the dominant ideology contained in the film Like & Share (2022). The theory used is Standpoint Theory which is supported by radical feminism. In this research, the application of John Fiske's semiotic analysis is carried out through 3 levels of coding, namely the level of reality, representation and ideology. From the research results, it was found that there were female voices in the film Like & Share (2022). Women's voices can be seen at the level of reality in aspects of appearance, behavior, expression, gestures, speech, make-up and environment. Then the woman's voice at the level of reality is emphasized by the level of representation which contains elements of camera, editing, music, sound effects and lighting. So from the reality level and representation level, it is found that there is a feminist ideology, namely radical feminism. However, of the total of 66 scenes, only 13 scenes in this film show female voices. This shows that this film is still lacking in presenting women's voices even though the initial aim of making Like & Share was as a campaign to eliminate violence against women. This film still shows the existence of patriarchal ideology and the use of a male perspective in the film.